2013
DOI: 10.7860/jcdr/2012/5098.2674
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Utility of Bact/ALERT and Nested PCR in the Diagnosis of Tuberculous Meningitis

Abstract: Objective: The early laboratory diagnosis of Tuberculous Meningitis (TBM) is crucial, to start the antitubercular chemotherapy and to prevent its complications. However, the conventional methods are either less sensitive or time consuming. Hence, the diagnostic potentials of BacT/ALERT and Polymerase Chain Reaction (PCR) was evaluated in this study. Material and Method:The study group comprised of 62 cases and 33 controls. The cases were divided according to Ahuja's criteria into the confirmed (two cases), hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
0
1
Order By: Relevance
“…Although the study of Sastry and Sandhya Bhat (2013) in India which was carried out on CSF specimens using IS6110 -nested PCR, 40.3% positive rate was achieved which was higher than our findings, probably due to their larger sample size, as the number of CSF specimens in this study was too few to make any conclusion. Also Alfonso et al (2002), in Colombia, reported a positivity rate of 74% by applying nested PCR targeting mtp40 on clinical specimens (urine, sputum, CSF, etc.…”
Section: Discussioncontrasting
confidence: 88%
“…Although the study of Sastry and Sandhya Bhat (2013) in India which was carried out on CSF specimens using IS6110 -nested PCR, 40.3% positive rate was achieved which was higher than our findings, probably due to their larger sample size, as the number of CSF specimens in this study was too few to make any conclusion. Also Alfonso et al (2002), in Colombia, reported a positivity rate of 74% by applying nested PCR targeting mtp40 on clinical specimens (urine, sputum, CSF, etc.…”
Section: Discussioncontrasting
confidence: 88%